2000
DOI: 10.1002/1097-4644(20010201)80:2<248::aid-jcb140>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential insulin-like growth factor (IGF)-independent interactions of IGF binding protein-3 and IGF binding protein-5 on apoptosis in human breast cancer cells. Involvement of the mitochondria.

Abstract: We have demonstrated previously in Hs578T cells that insulin-like growth factor binding protein (IGFBP)-3 can significantly accentuate ceramide (C2)-induced apoptosis, but has no effect on cell death induced by integrin detachment [using an arginine-glycine-aspartic acid (RGD)-containing peptide]. In contrast we found that IGFBP-5 could inhibit apoptosis induced by either C2 or integrin detachment. It is now clear that the mitochondria not only provide the energy required for cell viability, but can also play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…Recent studies have indicated that IGFBPs may act independently of IGFs to induce apoptosis in other cell systems (Nickerson et al, 1997;Perks et al, 2000); however, when MECs were incubated with 10 nM IGFBP-5 or -3 alone apoptosis was not significantly increased compared to serumstarved cells. A modest survival effect was seen although this was not statistically significant.…”
Section: Igf-i-mediated Survival Is Inhibited By Igfbp-5 and -3mentioning
confidence: 96%
“…Recent studies have indicated that IGFBPs may act independently of IGFs to induce apoptosis in other cell systems (Nickerson et al, 1997;Perks et al, 2000); however, when MECs were incubated with 10 nM IGFBP-5 or -3 alone apoptosis was not significantly increased compared to serumstarved cells. A modest survival effect was seen although this was not statistically significant.…”
Section: Igf-i-mediated Survival Is Inhibited By Igfbp-5 and -3mentioning
confidence: 96%
“…Similarly, IGFBP-5 improves the survival of breast cancer cells. This function appears to be IGF-independent and to rely on an apoptosis-inhibiting effect triggered via a pathway which does not involve the mitochondria (Perks et al 1999(Perks et al , 2000. However, breast carcinoma cells apparently are also susceptible to growth inhibitory signals of IGFBP-5 at certain stages if triggered by appropriate signals such as vitamin D (Rozen & Pollak 1999), anti-oestrogens (Parisot et al 1999) or androgen deprivation (Nickerson et al 1999).…”
Section: Igfbp-5 and Cancermentioning
confidence: 99%
“…IGFBP-5 may have direct and/or indirect anti-apoptotic activity (31)(32)(33)(34). Therefore, IGFBP-5 up-regulation, in an Akt-dependent manner, may be of particular importance to the cardioprotective effects of Akt.…”
Section: Figmentioning
confidence: 99%